Detection of Laylat Al-Qadr in Ramadan Using Iqra' Algorithm Based on Unique Anomaly as Luxlier Data Detection to Prove the Truth Signs of Islam - Cholissodin, Imam; Shampton, Achmad; Soebroto, Arief Andy (Proceedings of the International Conference on Green Technology; Vol 13 No 1 (2023): Proceeding of International Conference on Green TechnologyDO - 10.18860/icgt.v13i1.2716, 2024)
This study is related to the importance of increasing the understanding on the use of advanced technology on the signs of truth from Allah SWT contained in the Qur'an and Hadith so that they can be easily understood by many people, especially those outside Islam, to show that Islam is a very scientific and rahmatan lil 'alamin. Therefore, in this research, a collaboration is carried out between the fields of science and technology from Data Science as the approach of identification the Laylat al-Qadr (LQ) occurrence and why it only occurs one day in the Ramadan using the iQRa' Algorithm as the main research proposal and contribution with Artificial Intelligence (AI), Machine Learning (ML) and implementation code. From the results, it was suggested that the identification of the 2022 LQ day falls on 23 Ramadan 1443 H, which have been tested from 21 cities along 29-30 days data, from the beginning to the end of Ramadan 2022.